Fungsi Komunikasi dalam T ransmisi Nilai-nilai Keagamaan pada Organisasi Kerohanian Islam (Rohis) di SMA Negeri 1 Purworejo - Umi Muzayanah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
A process of value transmission can not be separated from the role of communication that involves communicators as messengers and communicants as the recipient of the message. Similarly, in the process of transmitting religious values by the organization of Spirituality of Islam (Rohis), communication becomes one of the determinants of the success of Rohis’s mission in the fostering of Islam in school. Using a qualitative approach, this research attempts to describe the communi- cation model built by Rohis SMAN 1 Purworejo in transmitting reli- gious values to Muslim students at school. Through interviewing tech- niques, observation, and documentation obtained some research find- ings. First, the communication model built by Rohis SMAN 1 Purworejo is interactional communication, which provides an opportunity for in- teraction between the messenger and the recipient of the message. Sec- ond, Rohis SMAN 1 Purworejo applies formal transmission model through structured activities, whereas non-formal transmission is re- flected from Rohis social interaction with other students in school envi- ronment.